ASSOCIAÇÃO ENTRE FATORES CLÍNICOS E MOVIMENTOS GERAIS COM TREMORES EM RECÉM-NASCIDOS PRETERMO NA UNIDADE DE TERAPIA INTENSIVA NEONATAL (Movimenta (ISSN 1984-4298), 2022)
Objective: To identify and characterize the occurrence of tremors and explore the association between clinical factors and general movements with the number of affected limbs and the duration of tremor in preterm newborns in a Neonatal Intensive Care Unit (NICU). Methods: A cross-sectional study was carried out in a NICU with 26 beds, with an average annual hospitalization of 120 preterm newborns. Tremors were identified by watching newborns' videos, recording the number of affected limbs and the maximum tremor time. Clinical factors were recorded from medical records and the classification of general movements was dichotomized into normal and abnormal categories, through the General Movements Assessment. Association between the variables was verified using the Spearman correlation test. Results: Twenty-nine preterm newborns were evaluated; all presented tremor at the 36th week of gestational age. There was significant association between the number of limbs that presented tremor and the use of phenobarbital (rho=0.51; p=0.005) and between the duration of tremor and the abnormal classification of general movements (rho=0.47; p= 0.01). Conclusion: The use of phenobarbital and the abnormal classification of general movements were associated with the characteristics of tremors in NICU preterm newborns, which supports the importance of assessing general movements in infants with tremors and conducting further studies to investigate the effect of medication use in this population.